Pengaruh Desain Template Siap Pakai, Layanan Konsultasi Desain dan Kemudahan Pemesanan Online terhadap Minat Beli Konsumen di Toko Percetakan Bahtera Batam - Desta Biran Fhajriah A (Jurnal Manajemen Riset Inovasi, 2026)
This study aims to analyze the influence of ready-to-use template designs, design consultation services, and the ease of online ordering on consumer purchasing interest at the Bahtera Batam Printing Shop, both partially and simultaneously. This study used a quantitative approach with a survey method. The population in this study was all consumers who made purchases at the Bahtera Batam Printing Shop, with a sample size of 123 respondents. The sampling technique used non-probability sampling with a purposive sampling method. Data collection was conducted through questionnaires measured using a Likert scale. Data were analyzed using multiple linear regression, hypothesis testing (t-test and F-test), and coefficient of determination testing using SPSS.The results of the partial test (t-test) indicate that ready-to-use template designs have a positive and significant effect on consumer purchasing interest (significance value 0.005 < 0.05). Design consultation services also have a positive and significant effect on consumer purchasing interest (significance value 0.002 < 0.05). Similarly, the ease of online ordering had a positive and significant effect on consumer purchase intention (significance value 0.001 < 0.05). Simultaneous testing (F-test) demonstrated that ready-to-use template designs, design consultation services, and ease of online ordering collectively had a positive and significant effect on consumer purchase intention at Bahtera Batam Printing Shop (significance value 0.000 < 0.05). Based on the coefficient of determination test (Adjusted R-square), 48.1% of the variation in consumer purchase intention was influenced by these three services, while the remaining 51.9% was explained by factors outside this research model.